Efficiency and Status in Polygynous Pastoralist Households. Issue 2 (1st February 2021) - Hidrobo, Melissa; Hoel, Jessica B.; Wilson, Katie
Abstract: Decision-making structures may be different across polygynous and monogamous households, leading to different economic outcomes and requiring different targeting of anti-poverty programmes. We study efficiency in semi-nomadic pastoralist households in Northern Senegal with lab-in-the-field games. We find that monogamous and polygynous families are equally productively inefficient overall. However, average contributions at the household level mask differences across dyads. Junior wives receive less but give more to their husbands than senior wives, leaving junior wives worse off than other household members.